2015
DOI: 10.3171/2015.2.spine14746
|View full text |Cite
|
Sign up to set email alerts
|

Complications and outcomes of vasopressor usage in acute traumatic central cord syndrome

Abstract: OBJECT The optimal mean arterial pressure (MAP) for spinal cord perfusion after trauma remains unclear. Although there are published data on MAP goals after spinal cord injury (SCI), the specific blood pressure management for acute traumatic central cord syndrome (ATCCS) and the implications of these interventions have yet to be elucidated. Additionally, the complications of specific vasopressors have not been fully explored in this injury condition. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 28 publications
(45 reference statements)
0
54
0
3
Order By: Relevance
“…Our audit of 42 patients concluded that insertion of the pressure probe and ISP monitoring for up to a week are safe 7 . However, actively increasing SCPP requires vasopressors, which may produce complications such as cardiac dysrhythmias, especially in older patients 22,23 . We previously showed that, after TSCI, the spinal cord swells and is compressed by the dura 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Our audit of 42 patients concluded that insertion of the pressure probe and ISP monitoring for up to a week are safe 7 . However, actively increasing SCPP requires vasopressors, which may produce complications such as cardiac dysrhythmias, especially in older patients 22,23 . We previously showed that, after TSCI, the spinal cord swells and is compressed by the dura 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The results called into question the clinical benefit of applying MAP goals in the population with acute traumatic central cord syndrome. 21 Our series similarly demonstrates high complication rates within the subset of patients with penetrating SCIs. Penetrating injuries are also associated with a poor prognosis because they often result in complete cord transection and, as shown by our series of cases, in hemorrhagic injury.…”
Section: Vasopressor Administration For Penetrating Scismentioning
confidence: 62%
“…These cases may require anterior stabilization, or in addition may need posterior fixation or 360 degree circumferential fusion depending upon degree of spinal instability, clinical feature and progressive neurological deterioration, extent of neural canal compromise, degree of loss of vertebral height, facetal dislocation, rotational component, associated fracture of lamina and associated systemic injury. [8][9][10][11][12] An intensive resuscitation and maintainace of adequate blood pressure under vasopressor support with a mean arterial pressure of 85 mm Hg should be maintained for at least seven days following acute spinal cord injury need to highlighted to improve the neurological outcome,. As in resource starved centres, inadequate infrastructure not only delay in referral to hospital and many of these cases does not get adequate treatment and monitoring in the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Readdy et al conclude after analysis of 34 cases with acute traumatic central cord syndrome, who were administered vasopressor agents to maintain targeted mean arterial pressure, definitely led to improvement in neurological status in all the treated patients. [11] Catapano et al highlighted an important social issue and tried to explore the widely prevalent biased attitude of physician as well as paramedical staff towards spinal cord injury victims, especially those with complete neurological deficit while providing resuscitation or inside the hospital care and called for immediate and radical social change on humanitarian approach . Further, such patient should also be helped to get social inclusion.…”
mentioning
confidence: 99%